Disaster-vulnerable community perception related to pre-earthquake natural phenomena in west sumatera as part of disaster preparedness. Issue 1 (March 2021) - Fadilah, M; Maryani, E; Permanasari, A; Riandi, R
Abstract: This article aims to describe the perception of disaster-vulnerable community-related natural phenomena before the occurrence of earthquakes. This research applies the survey methods and purposive sampling. A total of 229 respondents from earthquake-prone districts respond to questionnaires and interviews. The data are analysis quantitatively (percentages). The finding informs that many people are well acquainted with earthquake characteristics, threats and risks of earthquake impacts in West Sumatra based on scientific knowledge. Amongst the four regions of the community, the Padang Pariaman people experience nature and animal anomaly before the earthquake. The two unusual phenomena which are recognized are the rising temperature and the appearance of a vertical tornado-like cloud, beside nervousness of a dog, cat, cow, and bird. However, the community has not employed this perception based knowledge as a recommendation to act in quake preparedness. Beliefs in religious have much-driven people in responding to the threat of hazard. It can be concluded that even though the community perceives natural changes before the shock, but these phenomena have not become part of disaster preparedness yet. It is being a challenge for further research to build an earthquake preparedness approach which considers scientific knowledge, local knowledge and values, and trust to the Gods' provisions